Sikap dan Perilaku Swamedikasi Dismenore Primer pada Mahasiswi Farmasi Universitas Ngudi Waluyo : Attitudes and Behavior of Self-Medication for Primary Dysmenorrhea among Pharmacy Students at Ngudi Waluyo University - Haswan, Dedi; Pujiastuti, Anasthasia; Pratiwi, Neli Diah (Indonesian Journal of Pharmacy and Natural Product, 2024)
Women experience pain that varies in intensity for each individual. Menstrual pain can be treated using pharmacological and non-pharmacological therapy. The use of therapy for dysmenorrhea can improve the quality of life of sufferers. The Pharmacy Study Program at Ngudi Waluyo University is dominated by female students where menstrual pain will be an obstacle that affects their academic and daily activities. The aim of this study was to determine the attitudes and behavior of students from the Pharmacy Study Program at Ngudi Waluyo University when experiencing primary dysmenorrhea and to assess the strength of the correlation between the intensity of dysmenorrhea pain and therapy. The method used in this research is descriptive analysis with simple random sampling data collection techniques. Data was analyzed using the SPSS 25 statistical application. Based on the data obtained, 27.11% of respondents used therapy, and 72.89% of respondents did not use therapy. Reducing the pain intensity of primary dysmenorrhea has a correlation of 0.520 (moderate) with the use of therapy. Based on statistical tests on academic activities (sig. 0.006) and daily activities (sig. 0.000) which shows that there is an influence of primary dysmenorrhea on the academic and daily activities of respondents, but it has a weak correlation, namely 0.212 and 0.306 respectively. The use of therapy can reduce the intensity of pain in primary dysmenorrhea, however, many do not use therapy when experiencing primary dysmenorrhea and primary dysmenorrhea affects the respondents' academic and daily activities.   ABSTRAK Perempuan mengalami nyeri haid dengan intensitas yang berbeda pada setiap individu. Nyeri haid dapat diatasi menggunakan terapi farmakologi maupun non farmakologi.  Penggunaan terapi pada dismenore dapat meningkatkan kualitas hidup penderita. Prodi Farmasi Universitas Ngudi Waluyo didominasi oleh mahasiswi dimana nyeri haid akan menjadi kendala yang mempengaruhi aktivitas akademik maupun kesehariannya. Tujuan penelitian ini adalah untuk mengetahui sikap dan perilaku mahasiswi Prodi Farmasi Universitas Ngudi Waluyo ketika mengalami dismenore primer dan menilai kekuatan korelasi intensitas nyeri dismenore terhadap terapi. Metode yang digunakan pada penelitian ini adalah analisis deskriptif dengan teknik pengambilan data simple random sampling. Data dianalisis menggunakan aplikasi statistik SPSS 25. Berdasarkan data yang diperoleh, sebanyak 27,11% responden menggunakan terapi, dan 72,89% responden tidak menggunakan terapi. Penurunan intensitas nyeri dismenore primer mempunyai korelasi 0,520 (moderate) dengan penggunaan terapi. Berdasarkan uji statistik pada aktivitas akademik (sig. 0,006) dan aktivitas keseharian (sig. 0,000) yang menunjukkan terdapat pengaruh dismenore primer terhadap kegiatan akademik dan keseharian respoden, namun mempunyai korelasi yang lemah, yaitu masing-masing 0,212 dan 0,306. Penggunaan terapi dapat menurunkan intensitas nyeri pada dismenore primer, akan tetapi banyak yang tidak menggunakan terapi ketika mengalami dismenore primer dan dismenore primer mempengaruhi kegiatan akademik dan keseharian responden.